Interculturalidade e educação linguística crítica: diversidade cultural brasileira em livros didáticos de língua inglesa - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The main objective of this study is to reflect on the cultural diversity of the Brazilian people, the achievements and challenges that emerge from it, and how the intercultural traits of this society permeate textbooks for English language teaching and contribute to overcoming or exacerbating inequalities. Theoretically supported by the principles of critical interculturality (WALSH, 2009, 2019; CANDAU, 2020, 2021) and critical literacy (DUBOC, 2012, 2016; JORDÃO, 2013, 2016; MENEZES DE SOUZA, 2011), as well as the assumptions that highlight the importance of social representation in English textbooks (BALADELI, 2014; NASCIMENTO, 2016). The results were extracted from English language textbooks from the second edition of the Way to English for Brazilian Learners collection.The research was carried out using a qualitative approach and documentary research. According to the study carried out, the pedagogical material presents some texts that allow the discussion and formation of other meanings about reflection on Brazilian cultural diversity and respect for differences. However, it is noted that the analyzed teaching instrument has few representations of indigenous peoples and their roles, struggles, and rights in national society, reducing the possibilities of further discussions on the subject.
Interculturality and critical linguistic education: brazilian cultural diversity in english language textbooks
Keywords: Interculturalidade Crítica; Diversidade cultural brasileira; Letramento Crítico - Livro didático de inglês; Coleção Way to English for Brazilian Learners; Critical Interculturality; Brazilian cultural diversity; Critical Literacy - English textbook; Way to English for Brazilian Learners collection; LETRAS::LINGUAS ESTRANGEIRAS MODERNAS